Balaganjur Geger Bhaya, a Representation of the Phenomenon of Mount Agung Eruption | Balaganjur Geger Bhaya, sebuah Representasi Fenomena Erupsi Gunung Agung - I Komang Widiasa Mang Wid; Ni Ketut Dewi Yulianti (GHURNITA: Jurnal Seni Karawitan, 2023)
The Baleganjur Geger Bhaya percussion is a work that takes the concept or idea from the phenomenon of the eruption of Mount Agung. The process of creating the Balaganjur Geger Bhaya percussion involves a very original concept designed for the first time. The form and structure of this work still uses the Tri Angga concept, identified by the existence of Kawitan, Pengawak, dan Pengecet. The connection between the Balaganjur Geger Bhaya percussion and the eruption of Mount Agung is that it implies a situation of anxiety and fear among the people around MountAgung about the possibility of further eruptions. The situation is implemented into the title of the work "Geger Bhaya", Geger means panic and Bhaya means danger. Balaganjur Geger Bhaya was presented live as one of the performances at the 40th Bali Arts Festival (PKB). It was contested and performed on the open stage of Ardha Candra Art Center Denpasar. The author chooses the work of Balaganjur Geger Bhaya as a study because this work deals with natural phenomena and so far, no one has studied comprehensively aboutit. Keywords: Mount Agung, Eruption Phenomenon, Balaganjur Geger Bhaya